Recent advances in ocular drug delivery systems and targeting VEGF receptors for management of ocular angiogenesis: A comprehensive review - Soumya Narayana; Mohammed Gulzar Ahmed; B. H. Jaswanth Gowda; Pallavi K. Shetty; Arfa Nasrine; M. Thriveni; Nadira Noushida; A. Sanjana (SpringerOpen, 2021)
Abstract Background Angiogenic ocular diseases address the main source of vision impairment or irreversible vision loss. The angiogenesis process depends on the balance between the pro-angiogenic and anti-angiogenic factors. An imbalance between these factors leads to pathological conditions in the body. The vascular endothelial growth factor is the main cause of pathological conditions in the ocular region. Intravitreal injections of anti-angiogenic drugs are selective, safe, specific and revolutionized treatment for ocular angiogenesis. But intravitreal injections are invasive techniques with other severe complications. The area of targeting vascular endothelial growth factor receptors progresses with novel approaches and therapeutically based hope for best clinical outcomes for patients through the developments in anti-angiogenic therapy. Main text The present review article gathers prior knowledge about the vascular endothelial growth factor and associated receptors with other angiogenic and anti-angiogenic factors involved in ocular angiogenesis. A focus on the brief mechanism of vascular endothelial growth factor inhibitors in the treatment of ocular angiogenesis is elaborated. The review also covers various recent novel approaches available for ocular drug delivery by comprising a substantial amount of research works. Besides this, we have also discussed in detail the adoption of nanotechnology-based drug delivery systems in ocular angiogenesis by comprising literature having recent advancements. The clinical applications of nanotechnology in terms of ocular drug delivery, risk analysis and future perspectives relating to the treatment approaches for ocular angiogenesis have also been presented. Conclusion The novel ocular drug delivery systems involving nanotechnologies are of great importance in the ophthalmological sector to overcome traditional treatments with many drawbacks. This article gives a detailed insight into the various approaches that are currently available to be a road map for future research in the field of ocular angiogenesis disease management.